P579 Rates, predictive factors and effectiveness of ustekinumab intensification to 4- or 6-weekly intervals in Crohns's disease. (21st January 2022) - Derikx, L; Plevris, N; Su, S; Gros, B; Lyons, M; Siakavellas, S; Constantine-Cook, N; Jenkinson, P; O'Hare, C; Merchant, L; Noble, C; Arnott, I; et al.
Abstract: Background: The efficacy and safety of ustekinumab (UST) intravenous induction followed by 8- and 12- weekly maintenance was established in the UNITI controlled trial. These data report dose intensification for 12- to 8-weekly but not 4-weekly. The effectiveness of this strategy is an important, unanswered real-world question. We aimed 1) to assess the cumulative incidence of UST dose intensification to 4- or 6-weekly in patients with Crohn's disease (CD), 2) to identify factors associated with dose intensification, and 3) to assess the effectiveness and safety of this strategy. Methods: We performed a retrospective, observational cohort study in a tertiary IBD referral centre. All CD patients treated with UST between 22 January 2015 and 28 October 2020 were identified from a prospective biologic prescription database. Subsequently, data on IBD phenotype, UST interval, drug survival, and corticosteroid-free remission were collected. Dose intensification and drug survival were established with (one minus) Kaplan Meier curves. Logistic regression models were used to identify factors independently associated with dose intensification. Results: 163 CD patients (male: 71/163 [43.6%]; median disease duration 9.5 years [IQR 4.8–17.1]) were treated with UST, with median follow-up time of 20.3 months (13.4–38.4). 21/163 patients (12.9%) were biologic naïve, whereas 142 patients (87.1%) were previously treated with one (n=100, 61.3%) or two biologic therapies (n=42, 25.8%). During follow-up, 55/163 patients (33.7%) underwent dose intensification to a 4-weekly (n=50, 30.7%) or 6-weekly (n=5, 3.1%) interval. Median time to dose intensification was 6.1 months (3.9–11.0); after 1 year 29.9% were escalated to 4- or 6-weekly UST. Prior exposure to both anti-TNF and vedolizumab (HR 9.5; 1.3–70.9) as well as concomitant steroid use at start of UST (HR 1.8; 1.0–3.1) were independently associated with dose intensification (Figure 1; non-significant: age, CD behaviour, perianal disease activity and UST start dose). Following dose intensification 62.6% patients (29/55) remained on UST beyond 1 year (median time to discontinuation 5.2 months; Figure 2). No licensed treatment options remained in 12/29 patients. At the end of follow-up, (median 8.9 months [4.3–14.8] following dose intensification) 27.8% (15/54) were in corticosteroid-free and clinical remission. Figure 1 Conclusion: One third of CD patients treated with UST will undergo dose intensification to a 4- or 6-weekly interval within the first year. Patients who failed two or more biologics were more likely to dose intensify. These are a very refractory group of CD patients, the majority of whom have no licensed treatment options available.